STOCK MARKET PRICES AND FOREIGN EXCHANGE RATE INTERACTIONS IN NIGERIA: EVIDENCE FROM COINTEGRATED VAR MODEL - Kuhe, David Adugh; Torruam, Japheth Terande; Yaweh, Blessing Iveren (FUDMA Journal of Sciences, 2025)
The relationship between stock prices and foreign exchange rates has been a subject of ongoing academic debate, with empirical findings often yielding mixed results. This study investigates the dynamic link between stock market prices and the foreign exchange rate in Nigeria by analyzing secondary monthly time series data on the All Share Index, Naira/USD exchange rate, and money supply spanning January 2009 to December 2024. The analysis employs the Ng-Perron modified unit root test, Johansen Cointegration technique, Vector Autoregressive (VAR) model, impulse response function, variance decomposition and the Granger causality test using the modified Wald approach. Findings indicate that all variables are integrated of order one, yet no long-term cointegrating relationship exists among them. The VAR model reveals a degree of inertia in the behaviour of stock prices, exchange rates, and money supply in the short term. Stock market prices in Nigeria show a sluggish response to shocks in the exchange rate and money supply. Furthermore, neither exchange rate movements nor changes in money supply were found to significantly predict stock market prices, suggesting limited effectiveness of these variables as tools for stock market intervention. Granger causality tests also indicate the absence of causal relationships among the variables, implying that fluctuations in exchange rates and money supply do not significantly impact stock market performance in Nigeria. The study recommends that policymakers should not rely solely on exchange rate and money supply as tools for influencing stock market performance in Nigeria, but rather adopt broader macroeconomic and institutional strategies beyond exchange...